ANALYSIS OF SHARIA MARKETING MIX AND SERVICE QUALITY TOWARDS CUSTOMER SATISFACTION AT GRESIK VIVI DRINKING WATER REFILLING STATION - Malik, Ahmad Dahlan (Universitas Siliwangi, 2023)
This research is conducted to help customers in delivering the complaints in the form of product quality and the way of providing services of the subject research and the improvement of it using sharia marketing mix perspectives and service quality. This research is a quantitative study using the Partial Least Squares (PLS) method. The data collection method comes from primary data of distributing questionnaires to 126 respondents of Gresik Vivi Drinking Water Refilling Station customers. The results of this study indicate that product quality (X1), Price (X2) and Promotion (X4) have no significant effect on customer satisfaction (Y) and in the other words those variables need to be high concern of the owner of business to handle the improvement or handling the customer complaints. Meanwhile, the location (X3) and the service quality (X5) have a significant effect. This is indicated that those variables are more suitable for the customer satisfaction and need to be maintained by the owner in developing the business.Â